Analisis Tindak Tutur Lokusi, Ilokusi dan Perlokusi pada Film “3.600 Detik” Karya Charon - Simanjuntak, Agnes Abigael; Sagala, Florentina; E Sibuea, Johana Jojor; J Sitorus, Ruth Silvia Lisda; Yuhdi, Achmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Language is used as a means of communication between users. Through language, communication between users or speakers can occur well if there is the same understanding between speakers. When someone speaks, there is an interlocutor who will respond to his words. The formulation of the problem that will be discussed is the analysis of speech act events. This research aims to describe every sentence containing locutionary, illocutionary and perlocutionary events of the characters in the